2008
DOI: 10.1007/s10792-008-9240-4
|View full text |Cite
|
Sign up to set email alerts
|

The results of trabeculectomy using a sutureless scleral tunnel technique

Abstract: It appears that sutureless scleral tunnel trabeculectomy is a safe and effective drainage procedure for treating uncontrolled glaucoma. Larger-scale study is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…An absolute success rate at 6 months was 90%. Our results were better than that reported by Lai JSM et al [7] and Yadollah Eslami et al [9] in their studies. Lai JSM et al [7] observed an absolute success rate of 79%.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…An absolute success rate at 6 months was 90%. Our results were better than that reported by Lai JSM et al [7] and Yadollah Eslami et al [9] in their studies. Lai JSM et al [7] observed an absolute success rate of 79%.…”
Section: Discussioncontrasting
confidence: 87%
“…It is higher than that reported by Zaidi et al [10] (11.6%) and Yadollah Eslami. [11] in 2008, but lower than that reported by Lai JSM et al [7] (15.8%) and Yadollah Eslami et al [9] in 2009 (18%). Shallow anterior chamber was treated successfully with patching.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Aqueous outflow was also directed through a single outflow channel instead of two- or three-sided flap as in conventional trabeculectomy, thus maintaining the patency of created fistula. [16] The simplicity in scleral tunnel creation reduced the operation time and flap-related complications, which was an important advantage of SIGS over conventional trabeculectomy that was also reported by Jacob et al . [6] In the present study, scleral tunnel was left sutureless and the small conjunctival incision was closed by maximum two interrupted 10-0 nylon sutures, so that the perioperative problems involving the conjunctival and scleral flap that had been thought to be responsible for the postoperative complications of trabeculectomy were nearly eliminated.…”
Section: Discussionmentioning
confidence: 78%